Comparison of the Digene Hybrid Capture 2 Assay and Roche AMPLICOR and LINEAR ARRAY Human Papillomavirus (HPV) Tests in Detecting High-Risk HPV Genotypes in Specimens from Women with Previous Abnormal Pap Smear Results - Stevens, Matthew P; Garland, Suzanne M; Rudland, Elice; Tan, Jeffrey; Quinn, Michael A; Tabrizi, Sepehr N (Journal of Clinical Microbiology, 2007)
The development of cervical cancer is strongly associated with the presence of persistent high-risk (HR) human papillomavirus (HPV) infection. Recently, the commercially manufactured PCR-based Roche AMPLICOR (AMP) and LINEAR ARRAY (LA) HPV tests have become available for HPV detection. However, knowledge of their clinical performance compared to the U.S. Food and Drug Administration-approved Hybrid Capture 2 (HC2) assay is limited. This study evaluated the concordance between the HC2, AMP, and LA tests in detecting HR-HPV among a cohort of 1,679 women with previous abnormal Pap smear results. Overall, 1,393 specimens (81.3%) generated concordant results for HR-HPV presence or absence by the three assays. The concordance levels were substantial between the HC2 and AMP tests (84.4%, κ = 0.6419) and between the HC2 and LA tests (84.0%, κ = 0.6341) and nearly perfect between the AMP and LA tests (97.8%, κ = 0.9441). HR-HPV prevalence, as detected by the AMP or LA tests, was significantly higher among women with cytological or histological high-grade disease (CIN2 or greater) than that detected by HC2 (P < 0.0001). The AMP and LA tests exhibited greater sensitivity, but lower specificity, than HC2 for detecting HR-HPV among this cohort of women with underlying cervical abnormalities, particularly among subjects with histologically proven high-grade disease. Both PCR-based HPV tests may be valuable in the management of care for women with underlying cervical abnormalities, in predicting treatment success, and in studying the clearance or acquisition of new infections.